A mixed-elastohydrodynamic lubrication model of a capped-T-ring seal with a sectioned multi-material film thickness in landing gear shock absorber applications - Feria Alanis, Aaron; Sheikh Al-Shabab, Ahmed A.; Antoniadis, Antonis F.; Tsoutsanis, Panagiotis; Skote, Martin (MDPI, 2024)
Numerical investigations of capped T-ring (CTR) seals performance in reciprocating motion for landing gear shock absorber applications are presented. A lubrication model using the Elastohydrodynamic lubrication theory and deformation mechanics is developed in a multi-material contact zone, and a procedure for coupling fluid and deformation mechanics is introduced. By conducting Finite Element Method (FEM) simulations, the static contact pressure is obtained, which subsequently is used within the model developed herein consisting of a modified Reynolds equation and an asperity contact model, to calculate the fluid film pressure, and the deformation of the fluid channel is determined using an elastic deformation model applied to a multi-component multi-mechanical property channel. These computational results are used for estimations of the seal leakage and friction under various conditions. In addition, the influence of asperity orientation is compared with other parameters, such as sealing pressure and piston velocity. A correlation between asperity orientation and leakage was found, and a general trend of reduced leakage with longitudinally oriented asperities was established.
Keywords: 40 Engineering; 4017 Mechanical Engineering; 4012 Fluid mechanics and thermal engineering; mixed-elastohydrodynamic lubrication; capped T-ring seal; reciprocating seal; landing gears